The Screaming Mimi - Orabi, Abd Alrahman; Hassan, Arif (IIUM Journal of Case Studies in Management, 2019)
The case presents the work experience of an employee named Ali. He worked in a fashion designing and talent development company located in Kuala Lumpur, Malaysia. He was very excited and enthusiastic about the job as this was his job after graduating from a local university. He was looking forward to rewarding experiences as the job belonged to his interest and expertise. However, his enthusiasm and motivation soon waned as he encountered his lady boss and learned more about the work culture of the place. The company was headed by a lady who believed in theory X of management. She would scream, humiliate and bully employees, and would not care for them. She would arrive to office late in the afternoon or evening. No one would dare to leave the workplace until she left. She personified a good example of an abusive supervisor. Ali felt disgusted as he got no opportunity to show his talent and decided to leave the job.